Study on BGP route leak - Jia JIA; Zhi-wei YAN; Guang-gang GENG; Jian JIN (网络与信息安全学报)
With the rapid expansion of the scale of Internet,BGP plays a more and more important role in the Inter domain routing system.BGP has a lot of security risks,which result in prefix hijacking,AS_PATH hijacking and route leak attacks occuring frequently,causing serious threats to the Internet.In currently,the content introduction and security research mechanism were little,so a detailed study of BGP route leak was carried out.The BGP proto-col,route policy and established rules were introduced,six types of major route leak security incidents were analy-sised,the current security mechanisms and methods were summarized and compared to solve and detect route leak.In the last,a new prospect for the security and protection mechanism of route leak was proposed.